Creating alternate in-basket forms through cloning: Some preliminary results - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2007)
Research on constructing alternate forms of assessment center exercises is very scarce. This study examines the effectiveness of a cloning procedure (incident isomorphic approach) for developing alternate forms of a computerized in-basket. In this approach, original and alternate items are essentially similar (they are based on the same critical incident), while being superficially different (they are situated in a different context). Results showed there was no significant difference between the overall in-basket score across the alternate forms. In addition, these overall scores correlated .66, with projected estimates for the full in-basket approaching .80. Implications and limitations of the use of cloning in designing alternate assessment center exercises are discussed.